Mass spectrometric characterisation of the circulating peptidome following oral glucose ingestion in control and gastrectomised patients. (28th July 2020) - Kay, Richard G.; Foreman, Rachel E.; Roberts, Geoff P.; Hardwick, Richard; Reimann, Frank; Gribble, Fiona M.
Abstract : Rationale: Meal ingestion triggers secretion of a variety of gut and endocrine peptides important in diabetes research which are routinely measured by immunoassays. However, similarities between some peptides (glucagon, oxyntomodulin and glicentin) can cause specificity issues with immunoassays. We used a liquid chromatography/tandem mass spectrometry (LC/MS/MS) methodology to unambiguously monitor multiple gut peptides in human plasma. Methods: A simple acetonitrile‐based protein precipitation step, followed by evaporation and solid‐phase extraction, removed high‐abundance proteins from samples prior to nano‐LC/MS/MS analysis on an Orbitrap Q‐Exactive Plus mass spectrometer using a data‐dependent methodology. Database searching using PEAKS identified multiple gut‐derived peptides, including peptides in the mid‐pg/mL range. The relative levels of these and previously characterised peptides were assessed in plasma samples from gastrectomised and control subjects during an oral glucose tolerance test. Results: Analysis of plasma extracts revealed significantly elevated levels of a number of peptides following glucose ingestion in subjects who had undergone gastrectomy compared with controls. These included GLP‐1(7–36), GLP‐1(9–36), glicentin, oxyntomodulin, GIP(1–42), GIP(3–42), PYY(1–36), PYY(3–36), neurotensin, insulin and C‐peptide. Motilin levels decreased following glucose ingestion. Results showed good correlation with immunoassay‐derived concentrations of some peptides in the same samples. The gastrectomy group also had higher, but non‐glucose‐dependent, circulating levels of peptides from PIGR and DMBT1. Conclusions: Overall, the approach showed that a fast, generic and reproducible LC/MS/MS methodology requiring only a small volume of plasma was capable of the multiplexed detection of a variety of diabetes‐related peptides.